Herd protection of unvaccinated adults by oral cholera vaccines in rural Bangladesh. Issue 3 (29th November 2018) - Ali, Mohammad; Kim, Peter; Zaman, K; Clemens, John
Abstract: Background: Past research has suggested that the most cost-effective approach to using oral cholera vaccines (OCVs) to control endemic cholera may be to target only children <15 y of age. However, the assumption that vaccination of children with OCVs protects unvaccinated adults has never been tested. Methods: We reanalyzed the data of an OCV trial in Bangladesh in which children 2–15 y of age and women >15 y of age were allocated to OCV or placebo and assessed herd protection by relating the risk of cholera in each nonvaccinated adult (>15 y) to OCV coverage (OCVC) of residents residing in virtual clusters within 500 m of the residence of that unvaccinated adult. Results: The risk of cholera in unvaccinated adults decreased by 14% with each 10% increase of OCVC of all targeted age groups (95% 7 to 21%, p=0.0004). Also, the risk of cholera in unvaccinated adults decreased by 13% with each 10% increase in OCVC of children 2–15 y of age (95% CI 6 to 20%, p=0.0007). A high correlation between levels of OCVC of children and adult females precluded an assessment of the herd protection of unvaccinated adults by vaccinating children <16 y of age, independent of concomitant vaccination of adult women. Conclusions: Unvaccinated adults benefitted from herd protection conferred by OCVs in this trial. Vaccination of children may be sufficient to confer this protection, but this possibility needs to be evaluated in further studies.